EFFICACY OF HERBAL AND NONSTEROIDAL ANTI-INFLAMMATORY DRUGS IN THE THERAPY OF DYSMENORRHEA IN WOMEN WITH CONGENITAL UTERUS ANOMALIES - Veresnyuk, N.S.; Pyrohova, V.I.; Piniazhko, O.B. (World of Medicine and Biology, 2019)
Dysmenorrhea is the most common gynecological problem in women which negatively affects patients’ quality of life. The present study compared the efficacy and analized the average cost of Vitex agnus-castus and mefenamic acid in the treatment of dysmenorrhea in women with non-obstructive congenital uterus anomalies. This double-blind clinical trial was carried out in 42 women who were randomly divided into two groups. Dysmenorrhea severity by VAS and quality of life by SF-12 were assessed at baseline and three menstrual cycles throughout the treatment. It was found that at the end of the treatment, VAS scores were significantly fell in both groups compared to before intervention values (P